2015
DOI: 10.1080/00036846.2015.1051657
|View full text |Cite
|
Sign up to set email alerts
|

Women empowerment and infant mortality in Bangladesh

Abstract: This study attempts to investigate the effects of women empowerment on infant mortality in Bangladesh. Four indicators have been considered to measure four dimensions of women empowerment: the level of education, participation in household (HH) decisions, autonomy in movements and employment status. The rotated factor analysis technique is used to construct the last three dimensions. The Weibull parametric survival model has been specified and estimated using the Bangladesh Demographic and Health Survey (BDHS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Multiparous women having higher odds of death for their neonate in this study might suggest large number of children for the woman which is known to deplete maternal nutrition [64] and in uence the newborn survival. Consistent with other studies [65,66], women's high empowerment status was signi cantly associated with neonatal mortality. It is evident that when mothers are more empowered, they are likely to be more educated and have better knowledge about healthcare behavior for themselves and their children, which might contribute for low risk of neonate death [23].…”
Section: Discussionsupporting
confidence: 90%
“…Multiparous women having higher odds of death for their neonate in this study might suggest large number of children for the woman which is known to deplete maternal nutrition [64] and in uence the newborn survival. Consistent with other studies [65,66], women's high empowerment status was signi cantly associated with neonatal mortality. It is evident that when mothers are more empowered, they are likely to be more educated and have better knowledge about healthcare behavior for themselves and their children, which might contribute for low risk of neonate death [23].…”
Section: Discussionsupporting
confidence: 90%
“…The odd ratio of urban is 1.04 suggesting that infants born in urban areas are expected to die more compared to their counterpart in the rural areas. However, this ratio is not significant, found similar results in the study [8]. In Model (2), socioeconomic variables, i.e., wealth quintiles and women education level are excluded.…”
Section: Logistic Regression Analysis Of Child Mortalitysupporting
confidence: 68%
“…Other reports have shown that maternal education is a significant factor influencing child survival (Caldwell, 2009;Osonwa et al, 2012). Hossain et al (2002) supported a direct causal relationship between mother"s education and child mortality. Waters et al (2004) observed that mother"s education is positively associated with a number of measures of infant and child health and nutritional status.…”
Section: Brief Literature Reviewmentioning
confidence: 68%